Analisis Efektivitas Platform Inovasify sebagai Sarana Pembelajaran Gratis dalam Transformasi Kemampuan Inovatif Masyarakat - Kamilah, Nafisatul; Habibah, Habibah; Ayu Yulia, Novi (Najah: Journal of Research and Community Service, 2024)
The development of community capabilities is often related to limited access to adequate educational resources. The Inovasify platform emerges as a solution that offers free learning to support the transformation of people's innovative capabilities. This research aims to analyze the effectiveness of Inovasify Platform in achieving this goal. The research methods used include a quantitative approach through a survey of platform users and an in-depth interview and content analysis of the platform. The results showed that the use of Inovasify significantly increased innovation knowledge and skills among users. In addition, it shows that providing access to free learning through digital technology can play an important role in empowering communities and driving socio-economic transformation. The findings indicate that the Inovasify Platform is effective as a free learning tool capable of transforming people's innovative capabilities, while promoting educational inclusion in the digital era.